2007
DOI: 10.1002/ejlt.200700098
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of butter oxidation by some phenolics

Abstract: The ability of some phenolic compounds to inhibit butter oxidation was evaluated. Peroxide values and thiobarbituric acid reactive substances were monitored during storage of butter at 50 7C and at 110 7C. Gallic acid, caffeic acid and catechin, each at 80 mg/L, inhibited butter oxidation at 50 7C to a degree equal to that of butylated hydroxyanisole (BHA) at 200 mg/L. Gallic acid, at 80 mg/L, was more effective than BHA, at 200 mg/L, in inhibiting butter oxidation at 110 7C. Present results indicate that some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…Çakmakçı et al stated that the PV for all samples, containing essential oil, reduce linked to concentration, with addition of 0.2% essential oil showing nearly equal antioxidant activity to BHT. In another study about inhibition of butter oxidation the PV of the control sample increased during storage, while oxidation in BHA supplemented butter progressed slowly . Other studies are similar to our study results .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Çakmakçı et al stated that the PV for all samples, containing essential oil, reduce linked to concentration, with addition of 0.2% essential oil showing nearly equal antioxidant activity to BHT. In another study about inhibition of butter oxidation the PV of the control sample increased during storage, while oxidation in BHA supplemented butter progressed slowly . Other studies are similar to our study results .…”
Section: Discussionsupporting
confidence: 91%
“…Milk fat forms primarily of triacylglycerols and phospholipids. In butter the phospholipids oxidize more rapidly than the triacylglycerol components . It is emphasized that the quality of the product is preserved with a suitable antioxidant or antioxidant mixture added to the fat and fatty food before oxidation starts, the oxidation is delayed and the shelf life is extended and many natural and synthetic antioxidant materials are used for this purpose .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Soulti and Roussis evaluated the ability of some phenolic compounds (gallic acid, caffeic acid, and catechin) to inhibit butter oxidation during storage. The results indicated that the natural antioxidants inhibited oxidation in a similar manner to butylated hydroxyanisole.…”
Section: Resultsmentioning
confidence: 99%